Предмет: Математика, автор: lesnikovaa546

Номер 438
Помогите пожалуйста

Приложения:

Ответы

Автор ответа: fatyassirom
1

f (x) = x³ - 3x² + 1

f (0) = 0³ - 3*0² + 1 = 0 - 0 + 1 = 1

f (0) = 1

f (-1) = (-1)³ - 3*(-1)² + 1 = -1 - 3 + 1 = -3

f (-1) = -3

f (0,5) = 0,5³ - 3*0,5² + 1 = 0,125 - 3*0,25 + 1 = 0,125 - 0,75 + 1 = -0,625 + 1 = 0,375

f (0,5) = 0,375

f (-3) = (-3)³ -3*(-3)² + 1 = -27 -3*9 + 1 = -27 -27 + 1 = -54 + 1 = -53

f (-3) = -53


lesnikovaa546: Спасибо)
Похожие вопросы
Предмет: Математика, автор: Аноним
Предмет: Математика, автор: КаРиНа1111211111